Churches and denominational education in the Toszek District in the years 1742–1817/1818 (Zaranie Śląskie, 2025)
The study focuses on the religious situation in the years 1742–1817/1818 in the Toszek district, located on the right bank of the so-called ‘Polish’ Upper Silesia, conditioned by the tolerant religious policy of the Prussian authorities. It discusses the still dominant structure of the Roman Catholic Church, as well as the Reformed churches, mainly Lutheran, which were restored after more than a century of Counter-Reformation in Habsburg Upper Silesia, and the construction of Jewish religious institutions, which was still in its infancy. During this period, education, which existed only at the primary level in towns and villages, was religious in nature, with little interference from the state authorities.
Keywords: Upper Silesia; Prussian district of Toszek from 1742 to 1817/1818; Roman Catholic Church; Evangelical Churches; Jewish religious communities; Universal religious education